Electrocatalysts: Pyrolysis of Self‐Assembled Iron Porphyrin on Carbon Black as Core/Shell Structured Electrocatalysts for Highly Efficient Oxygen Reduction in Both Alkaline and Acidic Medium (Adv. Funct. Mater. 3/2017). (January 2017) - Li, Jia; Song, Yujiang; Zhang, Gaixia; Liu, Huiyuan; Wang, Yiren; Sun, Shuhui; Guo, Xinwen
Abstract : Pyrolysis of self‐assembled iron porphyrin on carbon black generates core/shell structured non‐noble metal electrocatalysts composed of N‐doped graphene‐like layers uniformly coated on carbon. In article 1604356, Y. Song, S. Sin, and co‐workers demonstrate excellent ORR activity for the catalyst. High durability and methanol tolerance as well as direct 4e and indirect 4e process toward ORR in alkaline and acidic medium are shown.